Challenges of Teaching and Learning English for Airlines Staff Candidates: A Study from a Training Center - Anisa Putri Cahyani; Joko N. K.; Sumardi Sumardi (Universitas Muhammadiyah Semarang, 2018)
The growth of airlines industry in Indonesia triggers training centers to develop their courses; one of them is their English class. This study looks closer into an EOP course in an Indonesian training center, and reveals some challenges of teaching and learning English for Airlines Staff Candidates. Data are collected through some interviews with teachers and students, also document studies focusing on teaching materials, class activity, and final scoring within a training batch. Both teachers and students have issues which related one another hindering the objectives of teaching and learning that strongly impact the course output. The findings can support teaching evaluation, material development, ideas in teaching methodologies, and need analysis in aviation training.